Denture Impaction Causing an Upper Esophageal Diverticulum - Samargandy, Shireen (Case Rep Gastrointest Med, 2019)
BACKGROUND: Dentures are a common cause of inadvertent foreign body ingestion particularly in the elderly. Due to their radiolucent nature, they often present a diagnostic challenge to care providing physicians. CASE PRESENTATION: A 66-year-old female presented to our otolaryngology clinic with a 2-year history of dysphagia. Her physical examination was unremarkable. Computed tomography scan of the neck and barium swallow suggested Zenker diverticulum. She was planned for endoscopic diverticulotomy; however, during surgery, a foreign body was incidentally found and retrieved, which was a partial lower denture. The diverticulum resolved thereafter, and the patient's symptoms abated. CONCLUSION: The authors recommend evaluating the esophagus endoscopically first in cases of upper esophageal diverticular formation, even when planning an open repair approach, to rule out any concealed foreign bodies.